Innovation in cities a driving force for knowledge flows: Exploring the relationship between high-tech firms, student mobility, and the role of youth entrepreneurship. (November 2022) - Marchesani, Filippo; Masciarelli, Francesca; Doan, Hung Quang
Abstract: Cities have increasingly asserted their central role in the national economy and in developing and promoting knowledge and innovation at local and national levels. Scholars, economists, and policymakers have examined the effects of innovation in this field as well as the resulting impact on the competitiveness and attractiveness of cities, regions, and urban areas. In the knowledge age, the importance of new generations and the trend towards high-skilled human capital are key factors in urban and national development. In this study, we aim to examine the role played by high-tech firms in the city context and its influence on the attraction of knowledge flow and analyse the moderating role of youth entrepreneurship in those relationships. Using the Spatial Panel data model, we evaluated the student flow interconnections in 30 Italian cities for a 10-year period (2009–2019). As a result, we found that the city attractiveness in terms of student mobility is influenced by the capacity of cities to generate and promote innovation in terms of high-tech firms at the local and spatial levels. These findings suggest that local high-tech firms in cities can influence the knowledge inflow and students' mobility while youth entrepreneurship in cities positively affects this relationship. The obtained results could serve as a good basis to enhance the city development policies in terms of innovation and knowledge, as well as the implementation of smart city projects. Highlights: We describe the relationship between innovative firms in cities and the attraction of knowledge using data on innovative and high-tech start-ups over a 10-year period. Moreover, we analyse the mediating role of youth entrepreneurship in the city as a driving force in the relationship between knowledge and innovation. Our findings indicate that a strong presence of high tech-start-ups in the city increases its competitiveness by attracting knowledge from other cities and regions. The city's ability to develop and promote youth entrepreneurship increases its competitiveness by attracting knowledge and supporting the development of a high-tech sector.